El discurso anarquista en dos documentales sobre la Segunda República y la Guerra Civil realizados durante la Transición - Jaime Céspedes (Cahiers de Civilisation Espagnole Contemporaine)
This article focuses on two anarchist documentary films about the Second Spanish Republic and the Spanish Civil War released Turing the Transition to democracy: Entre la esperanza y el fraude: España, 1931-1939 (by Cooperativa de Cine Alternativo, 1976) and Por qué perdimos la guerra (by Diego Abad de Santillán, 1978). The author studies these documentaries in their historical and ideological context and analyses their analogies and their differences in the light of their common aim: to oppose both to the Francoist version of the recent History of Spain and to the Communist version of this History.